Efficacy and safety of alirocumab and evolocumab: a systematic review and meta-analysis of randomized controlled trials. (3rd July 2019) - Guedeney, Paul; Giustino, Gennaro; Sorrentino, Sabato; Claessen, Bimmer E; Camaj, Anton; Kalkman, Deborah N; Vogel, Birgit; Sartori, Samantha; De Rosa, Salvatore; Baber, Usman; Indolfi, Ciro; Montalescot, Gilles; et al.
Abstract: Aims: The effect of low-density lipoprotein cholesterol-lowering therapy with alirocumab or evolocumab on individual clinical efficacy and safety endpoints remains unclear. We aimed to evaluate the efficacy and safety of alirocumab and evolocumab in patients with dyslipidaemia or atherosclerotic cardiovascular disease. Methods and results: We performed a review of randomized controlled trials (RCTs) comparing treatment with alirocumab or evolocumab vs. placebo or other lipid-lowering therapies up to March 2018. Primary efficacy endpoints were all-cause death, cardiovascular death, myocardial infarction (MI), and stroke. We estimated risk ratios (RR) and 95% confidence intervals (CI) using random effect models. We included 39 RCTs comprising 66 478 patients of whom 35 896 were treated with proprotein convertase subtilisin–kexin type 9 (PCSK9) inhibitors (14 639 with alirocumab and 21 257 with evolocumab) and 30 582 with controls. Mean weighted follow-up time across trials was 2.3 years with an exposure time of 150 617 patient-years. Overall, the effects of PCSK9 inhibition on all-cause death and cardiovascular death were not statistically significant ( P  = 0.15 and P  = 0.34, respectively). Proprotein convertase subtilisin–kexin type 9 inhibitors were associated with lower risk of MI (1.49 vs. 1.93 per 100 patient-year; RR 0.80, 95% CI 0.74–0.86; I 2 = 0%; P  < 0.0001), ischaemic stroke (0.44 vs. 0.58 per 100 patient-year; RR 0.78, 95% CI 0.67–0.89; I 2 = 0%; P  = 0.0005), and coronary revascularization (2.16 vs. 2.64 per 100 patient-year; RR 0.83, 95% CI 0.78–0.89; I 2 = 0%; P  < 0.0001), compared with the control group. Use of these PCSK9 inhibitors was not associated with increased risk of neurocognitive adverse events ( P  = 0.91), liver enzymes elevations ( P  = 0.34), rhabdomyolysis ( P  = 0.58), or new-onset diabetes mellitus ( P  = 0.97). Conclusion: Proprotein convertase subtilisin–kexin type 9 inhibition with alirocumab or evolocumab was associated with lower risk of MI, stroke, and coronary revascularization, with favourable safety profile.